Taking sides clashing views on controversional environment issue - Goldfarb 1935- (Dushkin/McGraw-Hill, 1999)
Introduces students to controversies in environmental policies and science. The readings reflect a variety of viewpoints and are staged as "pro" and "con" debates. Selections are organized around the areas of general issues, the environment and technology, and disposing of wastes.